Feasibility and implementation of Safer Kids – A parenting program to reduce child abuse. (January 2022) - van Leuven, Livia; Lalouni, Maria; Enebrink, Pia; Sorjonen, Kimmo; Forster, Martin
Abstract: Background: Child abuse is a world-wide problem causing long-term suffering for children and large costs to society. Parent-training programs have been shown to reduce harsh parenting but more research on parenting programs specifically addressing child abuse is needed. Objective: This study aimed at assessing the feasibility, implementation, and preliminary effectiveness of Safer Kids (SK); a structured parent-training program delivered immediately after parents are reported for child abuse. Participants and setting: Caregivers were eligible if they had been reported for child abuse to the Swedish social services and their child was 3–12 years old. Methods: Families were allocated to SK or intervention as usual (IAU) through a quasi-experimental design. Multilevel analyses and a Cox Proportional Hazard Model were used to assess between-group differences in risk factors for abuse and further child welfare reports. Results: In total, 67 families participated. SK was successfully implemented as an early-start intervention and most families completed the intervention. All agencies continued working with SK two years after the study, indicating sustainability of implementation. SK was more effective than IAU in reducing further child welfare reports up to 18 months from baseline. However, analyses of parent and child rated risk factors of re-abuse (abuse potential, wellbeing, and parent-child relationships) indicate none to small differences between conditions. Conclusions: SK can be successfully implemented within the social services and may be effective in reducing occurrence of further child welfare reports. The effects of SK need to be further evaluated in a randomized controlled trial. Highlights: Research on child abuse interventions is highly needed. Safer Kids is a parenting program delivered quickly after a report of child abuse . The intervention was successfully implemented within the social services. Safer Kids -parents were reported again to a lower extent than control group families. The effects of Safer Kids need to be further evaluated in larger trials.